A New High-Resolution Map of World Mountains and an Online Tool for Visualizing and Comparing Characterizations of Global Mountain Distributions - Roger Sayre; Charlie Frye; Deniz Karagulle; Jürg Krauer; Sean Breyer; Peter Aniello; Dawn J. Wright; Davnah Payne; Carolina Adler; Harumi Warner; D. Paco VanSistine; Jill Cress (Mountain Research and Development, 2018)
Answers to the seemingly straightforward questions “what is a mountain?” and “where are the mountains of the world?” are in fact quite complex, and there have been few attempts to map the mountains of the earth in a consistent and rigorous fashion. However, knowing exactly where mountain ecosystems are distributed on the planet is a precursor to conserving them, as called for in Sustainable Development Goals 6 and 15 of the United Nations 2030 Agenda for Sustainable Development. In this article we first compare 3 characterizations of global mountain distributions, including a new, high-resolution (250 m) map of global mountains derived from terrain characteristics. We show how differences in conceptual definition, methodology, and spatial resolution of source data can result in differences in the extent and location of lands classed as mountains. For example, the new 250-m resource documents a larger global mountain extent than previous characterizations, although it excludes plateaus, hilly forelands, and other landforms that are often considered part of mountain areas. We then introduce the Global Mountain Explorer, a new web-based application specifically developed for exploration, visualization, and comparison of these maps. This new open-access tool is an intuitive and versatile resource suitable for a broad range of users and applications.